Risk Factors for Lymph Node Metastasis in Papillary Thyroid Carcinoma: A Systematic Review and Meta-Analysis - Mao, Jingxin; Zhang, Qinghai; Zhang, Haiyan; Zheng, Ke; Wang, Rui; Wang, Guoze (Frontiers in Endocrinology, 2020)
Purpose: To investigate the risk factors that may predict the lymph node metastasis potential of these lesions and new prevention strategies in papillary thyroid carcinoma patients. Materials and Methods: A total of 9,369 papillary thyroid carcinoma patients with 37.17% lymph node metastasis were analyzed (Revman 5.3 software) in this study. The PubMed and Embase databases were systematically searched for works published since January 22, 2020. Results: The following variables were associated with an increased risk of lymph node metastasis in papillary thyroid carcinoma patients: age < 45 years (pooled OR = 1.52, 95% CI =1.14–2.01, p<0.00001); gender = male (pooled OR = 1.68, 95% CI = 1.51–1.87, p<0.00001); multifocality (pooled OR = 2.05, 95% CI = 1.45–2.89, p<0.0001); tumor size ≥1.0 cm (pooled OR = 3.53, 95% CI = 2.62–4.76, p < 0.00001); tumor location at the upper pole 1/3 (pooled OR =1.46, 95% CI = 1.04–2.04, p=0.03); capsular invasion + (pooled OR = 3.48, 95% CI = 1.69–7.54, p = 0.002); extrathyroidal extension + (pooled OR =2.03, 95% CI= 1.78–2.31, p < 0.00001). However, tumor bilaterality(pooled OR = 0.85, 95% CI = 0.54–1.34, p = 0.49) and Hashimoto’s thyroditis (pooled OR = 1.08, 95% CI = 0.79–1.49, p = 0.62) had no association with lymph node metastasis in papillary thyroid carcinoma patients. Conclusion: Our systematic review identified the following significant risk factors of lymph node metastasis in papillary thyroid carcinoma patients: age (< 45 years), gender (male), multifocality, tumor size (> 1 cm), tumor location (1/3 upper), capsular invasion and ETE. Bilateral tumors and Hashimoto’ s thyroiditis do not appear to be correlated with lymph node metastasis in papillary thyroid carcinoma patients.